Generally accepted rating principles: A primer - Krahnen, Jan Pieter; Weber, Martin (Journal of Banking & Finance, 2001)
Bank internal ratings of corporate clients are intended to quantify the expected likelihood of future borrower defaults. This paper develops a comprehensive framework for evaluating the quality of standard rating systems. We suggest a number of principles that ought to be met by “good rating practice”. These “generally accepted rating principles” are potentially relevant for the improvement of existing rating systems. They are also relevant for the development of certification standards for internal rating systems, as currently discussed in a consultative paper issued by the Bank for International Settlements in Basle, entitled “A new capital adequacy framework”. We would very much appreciate any comments by readers that help to develop these rating standards further.